PENINGKATAN KETERAMPILAN MENULIS WACANA GRAFITI DENGAN MENGGUNAKAN PENDEKATAN CTL PADA SISWA SMK MAARIF NU 1 AJIBARANG - Etin Pujihastuti (Faculty of Humanities, Universitas Jenderal Soedirman, 2018)
Teens creativity in producing graffiti discourse is a manifestation of their ability to express themselves. Various discourses of graffiti show patterns that can be understood as well as a form of adolescent ability to absorb information from the environment. Assessment of the topic of graffiti discourse generated by adolescents will lead to an understanding of the language of adolescence. This study focuses on trying to figure out the development of topics as a teenager creates a graffiti and knows the understanding of concepts and graffiti media. Some theories of discourse development are used to explore more about topic relation and information built into discourse. The results of this study are descriptions of the supporting components of conformity between the topic information and the development of graffiti discourse. CTL approach can be used as one of the solutions to improve students' graffiti writing skill. In addition to improving skills, Contextual Teaching and Learning (CTL) approach also plays an active role for students to remember experiences in their lives and more able to process words to be written in the form of graffiti discourse.